Phonographic Stylisation as a Means of Imitating Speech Anomalies: Challenges Faced by Literary Translators (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
This paper examines the phonographic stylisation means used to convey characters’ speech anomalies in English literature, focused on the works of Charles Dickens, Bernard Shaw, John R. R. Tolkien, and Zadie Smith. The paper also explores the functions of phonographic stylisation and discusses strategies for translating this phenomenon into Polish. The analysis covers three types of phonographic stylisation means: those arising from the speaker’s physical and emotional state, those used to stylize vernacular and dialectal speech, and those related to bilingual language interference. Despite authors’ careful efforts to maintain phonographic stylisation, translators might miss these subtleties, resulting in translations free from any speech anomalies whatsoever. However, recent studies show a trend towards translation strategies that closely imitate or analogically reproduce speech anomalies, thereby more accurately preserving phonographic stylisation in the target language, as seen in Tolkien’s The Hobbit and Smith’s Swing Time.